O12.4 Effects of enhanced STI partner notification counseling in cape town: randomized controlled trial. (14th July 2019) - Mathews, Catherine; Kalichman, Moira; Dewing, Sarah; Banas, Ellen; Dumile, Sekelwa; Mdlikiva, Amanda; Mdlikiva, Thembinkosi; Jennings, Karen; Lurie, Mark; Kalichman, Seth
Abstract : Background: People who contract STI in high-HIV prevalence settings such as South Africa are among the highest risk populations for HIV. Single-session behavioural interventions can reduce a person's risk for STI with added HIV prevention benefits, but promising prevention effects are undermined by untested, untreated partners with persistent STI. We tested a theory-based, single session behavioural risk reduction intervention with enhanced partner notification (ePN) counselling among people diagnosed with an STI, in Cape Town, South Africa. Methods: Participants were 1050 consenting adults diagnosed with STI at a community clinic. After the standard STI/HIV consultation and treatment, participants were randomly allocated to: (a) 20 minutes health education; (b) 45 minutes risk reduction skills counseling; or (c) 45 minutes risk reduction and ePN communication skills counseling. We measured participants' reports of PN to potentially exposed partners two weeks after diagnosis. Results: Participants were 527 men and 523 women, 20% HIV positive, enrolled between 2014 and 2017. There were no significant baseline differences between trial arms in number of reported main or casual sex partners. Two weeks after STI diagnosis (n=890, 85% retained), 77% of participants had notified a main partner of their STI and 57% had notified a casual partner. Conditions did not differ in rates of notifying main partners. However, participants receiving the ePN counseling (57%) were significantly more likely to have notified a casual partner compared to those in the health education (41%) and the risk reduction counseling (41%) arms, OR = 1.87, p <0.05. This pattern of differences did not differ by gender, with intervention effects significant for both men and women. Conclusion: The ePN intervention was effective at improving PN with casual partners. Although partner linkage to care was not measured, future analyses will determine whether there was a reduction in repeat STIs in index cases. Disclosure: No significant relationships.